PENGARUH TRANSFORMATIONAL LEADERSHIP TERHADAP UNIVERSITY PERFORMANCE MELALUI LEARNING ORGANIZATION DAN EMPOWERMENT SEBAGAI VARIABEL INTERVENING - Feby, Anthonius (Business Accounting Review, 2015)
University is an organization engaged in the education sector so it must have a goal to be achieved. Goals can be achieved if an organization has a good performance. Moreover, the era becomes more competitive, so it is also required that the performance of an organization should also be better. For that reason, it is a must for a university to recognize what variables that affect the performance of the university.        Data collected by distributing questionnaires to students who were in private universities in Surabaya. To avoid any wrong interpretation of the data obtained in the research process, then there were several steps that should passed as to test the validity and reliability through Partial Least Square (PLS). The results obtained showed that there was no significant affect of transformational leadership on the university performance. So in order to influence the university performance, transformational leadership required intervening variables such as learning organization and empowerment.